Advancements in Biosensor Materials: Synthesis and Applications of Carbon Nanotubes - Varjonen, Roosa (My University, 2024)
This thesis presents the most efficient synthesizing and purification methods for single- and multi-walled carbon nanotubes. The methods are viewed after their suitability for synthesizing or purification of single- or multi-walled carbon nanotubes or both. It is noticed that chemical vapour deposition and arc-evaporation are two of the most effective methods for carbon nanotube synthesis. In terms of purification, it is noticed that multi-step processes of purification are still needed, as not only one method is effective enough to achieve ultra pure carbon nanotubes. The characterization after purification is crucial to find out the properties of carbon nanotubesand their suitability for applications. Carbon nanotubes possess such electrical, mechanical and structural propertis, that they are a great material for biosensor applications, especially for electrochemical biosensors. Their detection capabilities are very effective compared to many other kind of biosensors.
Keywords: single-walled carbon nanotube, multi-walled carbon nanotube, synthesis, purification, characterization, biosensor, electrochemical biosensor